2008
DOI: 10.1186/1475-2875-7-142
|View full text |Cite
|
Sign up to set email alerts
|

Cohort study of the association of antibody levels to AMA1, MSP119, MSP3 and GLURP with protection from clinical malaria in Ghanaian children

Abstract: Background: Antigen-specific antibody-mediated immune responses play an important role in natural protection against clinical malaria, but conflicting estimates of this association have emerged from immuno-epidemiological studies in different geographical settings. This study was aimed at assessing in a standardized manner the relationship between the antibody responses to four malaria vaccine candidate antigens and protection from clinical malaria, in a cohort of Ghanaian children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
117
2
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(142 citation statements)
references
References 55 publications
22
117
2
1
Order By: Relevance
“…Antibody level increases with age and Pf carriage. Similar results were found previously [24][25][26][27]. Seroprevalence of anti-MSP1 _42 and anti-AMA1 antibodies increase with age.…”
Section: Smc Area (N=464) Control Area (N=275) P Valuesupporting
confidence: 91%
“…Antibody level increases with age and Pf carriage. Similar results were found previously [24][25][26][27]. Seroprevalence of anti-MSP1 _42 and anti-AMA1 antibodies increase with age.…”
Section: Smc Area (N=464) Control Area (N=275) P Valuesupporting
confidence: 91%
“…Although in our current study, age influenced IgM levels significantly, Dodoo et al 2008, showed an increase in IgG with age. [50] Ladeia-Andrade et al 2009, suggested an increasing malaria infection rate with increasing age, and induction of a significant anti parasite immunity amongst native Amazonians in Brazil. [51] Some studies have shown a negative correlation between IgM levels parasitemia levels.…”
Section: Discussioncontrasting
confidence: 77%
“…[55] Multivalent malaria vaccine development offer a better chance towards an efficacious malaria vaccine compared to monovalent vaccine. [50] Antibody levels against the four vaccine candidates were significant suggesting that an ideal malaria vaccine should target more than one antigen.…”
Section: Discussionmentioning
confidence: 99%
“…These results are also buttressed by independent experiments where the extent of correlation between antibody levels in a healthy state and during concurrent infection seemed to be antigen‐specific 43, 77. Polymorphic GPI‐anchored antigens [such as anti‐mitochondrial antibodies (AMA)‐1] often induced relatively higher antibody levels compared with conserved antigens (such as the Rhs) 43, 78, 79, 80. Responses also seemed site‐specific, with different levels observed for the same antigen in different sites 42, 43.…”
Section: Antibodies and Protection: What We Have Learnt So Farmentioning
confidence: 99%